2021
DOI: 10.1016/j.cub.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual history propagates down to early levels of sensory analysis

Abstract: Summary One function of perceptual systems is to construct and maintain a reliable representation of the environment. A useful strategy intrinsic to modern “Bayesian” theories of perception 1 , 2 , 3 , 4 , 5 , 6 is to take advantage of the relative stability of the input and use perceptual history (priors) to predict current perception. This strategy is efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 38 publications
(54 reference statements)
6
109
0
Order By: Relevance
“…Our results demonstrated that SD emerges at later stages than early sensory cortices 7 , likely involving task-related processing 5 . We cannot rule out the existence of SD at multiple stages of processing, as hypothesized in previous work 26 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our results demonstrated that SD emerges at later stages than early sensory cortices 7 , likely involving task-related processing 5 . We cannot rule out the existence of SD at multiple stages of processing, as hypothesized in previous work 26 .…”
Section: Discussionmentioning
confidence: 59%
“…Note that this conclusion refers to the source of SD. Our study does not exclude that SD ultimately leads to changes in the appearance of stimuli, i.e., that the source is post-perceptual but the site of action is perceptual 7 . Perceptual decisions 5 and higher-level cognitive biases may still propagate down to sensory cortices, directly distorting the appearance of stimuli 7 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One is that orientation signals of remembered stimuli may be reconverted back into retinotopic coordinates and projected back to V1 to interact with incoming signals. Indeed, feedback from higher areas may be one of the key mechanisms mediating serial dependence (Cicchini et al, 2021). Alternatively, even primary visual areas may display more allocentric properties than is commonly assumed.…”
Section: Discussionmentioning
confidence: 99%
“…This effect, known as serial dependence , probably reflects an optimisation strategy, where perceptual systems take advantage of temporal redundancies (the relative stability of the world) to improve signal to noise ratios, and hence efficiency (Cicchini et al, 2018). Much evidence suggests that serial dependence acts directly within perceptual circuitry, at early stages of information processing (Cicchini et al, 2021), including monaural auditory circuits (Hao Tam Ho et al, 2019) and primary visual cortex (V1) (St. John-Saaltink et al, 2016).…”
Section: Introductionmentioning
confidence: 99%